2009
DOI: 10.1016/j.jtcvs.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an autologous platelet clot in the pericardial sac: An experimental and clinical study

Abstract: Autologous platelet gel is unstable both in vitro and in vivo, whereas platelet-rich fibrin remains intact in vitro and, compared with autologous platelet gel, is less subject to degradation in pigs and in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Rademakers et al studied PRP degradation (platelet concentration *1000 • 10 3 platelets/mL) in an animal study and found that the weight of autologous platelet clots was reduced to 16% of the initial weight after 30 min of incubation in the pericardial sac. 42 In vivo tissue-related factors regulate the secretion of GFs from platelets. In addition, recruited or cotransplanted cells may also secrete GFs.…”
Section: Discussionmentioning
confidence: 99%
“…Rademakers et al studied PRP degradation (platelet concentration *1000 • 10 3 platelets/mL) in an animal study and found that the weight of autologous platelet clots was reduced to 16% of the initial weight after 30 min of incubation in the pericardial sac. 42 In vivo tissue-related factors regulate the secretion of GFs from platelets. In addition, recruited or cotransplanted cells may also secrete GFs.…”
Section: Discussionmentioning
confidence: 99%
“…In late 2008, Bayer HealthCare announced that marketing of the product was temporarily suspended pending review of additional clinical studies (Stamou et al 2009). In spite of the adverse events associated with the drug in CABG patients, clinical studies continue to explore the application of aprotinin in other indications, both prophylactic and therapeutic, where the control of pathophysiological inflammatory cascades is desirable (Maffulli et al 2008;Orchard et al 2008;Rademakers et al 2009). Further, the Nordic Group obtained the rights to Trasylol ® following the opinion issued by the Committee for Medicinal Products for Human Use of the European Medicines Agency in February 2012, recommending that the marketing authorization for aprotinin to be reinstated in the European Union.…”
mentioning
confidence: 99%